The Impact of Passive Alveolor Molding VS Nasoalveolar Molding on Cleft Width and Other Parameters of Maxilllary Growth in Unilateral Cleft Lip Palate (Medical Forum Monthly, 2024)
Objective: The basic aim of the study is to compare the effects of passive alveolar molding (PAM) and nasoalveolar molding (NAM) on cleft width and various parameters of maxillary growth in unilateral cleft lip palate.Study Design: This prospective cohort studyPlace and Duration of Study: This study was conducted at the Plastic and Reconstructive Surgery LUMHS Jamshoro during June 2023 to July 2024.Methods: Forty-five infants diagnosed with unilateral cleft lip palate were included in the study. They were divided into two groups based on the selected treatment approach: PAM and NAM. Cleft width measurements were recorded at specific time intervals during the treatment period. Additionally, maxillary growth parameters, including maxillary arch width, nasal symmetry, and columellar length, were evaluated over the course of the follow-up period.Results: Data was collected from 45 infant patients. There were 23 patients in PAM group and 22 patients in Nam group. Mean age was 4.5±2.45 months and there was 20 female patients and 25 male patients. Throughout the treatment period, both PAM and NAM groups exhibited progressive reduction in cleft width.Conclusion: It is concluded that both PAM and NAM interventions contribute positively to cleft width reduction, maxillary arch width, nasal symmetry, and columellar length. Notably, NAM exhibited superior efficacy in terms of faster cleft width reduction, improved nasal symmetry, and enhanced columellar length when compared to PAM.